2007
DOI: 10.1136/hrt.2006.088229
|View full text |Cite
|
Sign up to set email alerts
|

Wide spectrum of presentation and variable outcomes of isolated left ventricular non-compaction

Abstract: IVNC is associated with a broad spectrum of clinical and pathophysiological findings, and the overall natural history and prognosis may be better than previously thought. Adult patients with incidental or familial discovery of IVNC have an encouraging outlook, whereas those who have symptoms of heart failure, a history of sustained ventricular tachycardia or an enlarged left atrium have an unstable course and more severe prognosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
190
1
16

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 217 publications
(218 citation statements)
references
References 30 publications
11
190
1
16
Order By: Relevance
“…Recent study by Stollberger et al demonstrated that of 106 patients with LVNC who underwent a complete neurologic evaluation, 22 (21%) patients were diagnosed with a well-defined neuromuscular disorder and 68 patients (64%) a neuromuscular disorder of unknown etiology [5]. The rate of neuromuscular disease in this study is higher than previously described in other studies; however, patients in these previous studies were not routinely referred for neurologic evaluation [4,6,26,27]. The presence of a neuromuscular disorder in conjunction with LVNC was found to be associated with a higher mortality rate in this case series, 15% versus 0% [5].…”
Section: Associationscontrasting
confidence: 50%
See 2 more Smart Citations
“…Recent study by Stollberger et al demonstrated that of 106 patients with LVNC who underwent a complete neurologic evaluation, 22 (21%) patients were diagnosed with a well-defined neuromuscular disorder and 68 patients (64%) a neuromuscular disorder of unknown etiology [5]. The rate of neuromuscular disease in this study is higher than previously described in other studies; however, patients in these previous studies were not routinely referred for neurologic evaluation [4,6,26,27]. The presence of a neuromuscular disorder in conjunction with LVNC was found to be associated with a higher mortality rate in this case series, 15% versus 0% [5].…”
Section: Associationscontrasting
confidence: 50%
“…The occurrence rate of VT in adults with LVNC has been highly variable across studies (6-63%) which include a small number of patients, a high percentage of whom also have LV dysfunction as a strong risk factor for VT [3][4][5][6]10,22,25,26]. Thus, whether or not LVNC is an independent risk factor for VT is not known.…”
Section: Arrhythmiamentioning
confidence: 99%
See 1 more Smart Citation
“…[5][6][7][8][9][10][11][12][13][14][15] Typical complications include congestive heart failure, ventricular arrhythmias and thromboembolic events. [12][13][14]16,17 Recently, the association of LVNC with metabolic diseases, genetic syndromes and other cardiac abnormalities has been reported. [18][19][20] Genetic studies have shown sarcomere gene mutations in some patients with isolated LVNC similar to those with dilated or hypertrophic cardiomyopathy, and a recent study has found similar mutations in patients with Ebstein anomaly.…”
Section: Since Its First Description Left Ventricular Non-compactionmentioning
confidence: 99%
“…The electrophysiological study and/or the prophylactic implantation of ICD must be carefully considered. Competitive sports must be avoided and the first-degree relatives must be screened through Doppler echocardiographic studies 10 .…”
Section: Discussionmentioning
confidence: 99%